Dasyproctus helenae, a new species of solitary hunting wasp from India and a checklist of Dasyproctus Lepeletier de Saint Fargeau and Brullé, 1835 from the Indian subcontinent (Hymenoptera: Crabronidae: Crabronini) - Saini, Varun; Dey, Debjani (Zootaxa, 2022)
A new species of genus Dasyproctus Lepeletier de Saint Fargeau and Brullé, 1835 is described from India: Dasyproctus helenae Saini and Dey n. sp. A checklist is provided for all Dasyproctus species reported from the Indian subcontinent.